Analisis ADME Senyawa Aktif Cabai Jawa (Piper longum BI) secara In Silico Sebagai Kandidat Obat Antidepresan - Riryn Novianty (Turast: Jurnal Penelitian dan Pengabdian, 2020)
Depression is a mental disorder caused by an imbalance of neurotransmitters due to the catalytic activity of the MAO enzyme. This disease can be treated with antidepressants. Many in vivo studies have been carried out to examine the antidepressant activity of the active compounds in Javanese chili (Piper longum BI.). Still, the approach is in silico and has never been done. The purpose of this study was to see the potential of the three active compounds of Javanese chili (piperine, methyl piperate, and piperlonguminine) as antidepressants by analyzing their pharmacokinetic properties and drug-likeness via the SwissADME online site. All three compounds met ADME parameters (high GI-absorption, no P-gp inhibitor, no CYP2D6 inhibitor, yes BBB permeant and logKp < -2.5 cm/s) and obey Lipinski, Veber, Ghose rules, and have bioavailability score  0.55. The three compounds have the potential to be used as oral drugs based on the results of the bioavailability radar